2019
DOI: 10.4103/jips.jips_72_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the effect of electrolyzed oxidizing water on surface detail reproduction, dimensional stability and Surface texture of poly vinyl siloxane impressions

Abstract: Aim:The aim of this in vitro study was to comparatively evaluate the effect of chemical disinfectants on the surface detail reproduction, dimensional stability and surface texture of polyvinyl siloxane (PVS) impressions.Materials and Methods:The impressions were then divided into five groups (fifteen samples per group) and subjected to a ten minutes immersion with 2% glutaraldehyde (Group I), 1% sodium hypochlorite (Group II), freshly prepared electrolyzed oxidizing water (EOW) with different pH values - acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Future research on impression materials should analyze the influence of disinfection on their other properties, since it has been shown that some of these (e.g., surface roughness) can be significantly affected, particularly by chemical disinfectants [45,46]. Moreover, although our study applied a carefully designed methodology, simulating most of the oral conditions such as temperature and moisture, there is a need for more studies to confirm the lack of adverse effects of the proposed methods of disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Future research on impression materials should analyze the influence of disinfection on their other properties, since it has been shown that some of these (e.g., surface roughness) can be significantly affected, particularly by chemical disinfectants [45,46]. Moreover, although our study applied a carefully designed methodology, simulating most of the oral conditions such as temperature and moisture, there is a need for more studies to confirm the lack of adverse effects of the proposed methods of disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen reports 107,109–112,128,157–164 investigated the effects of EOW on dental biomaterial properties (Table 3, Table S1). One study 62 reported on the rusting of carbon steel burs immersed in different EOW solutions (acidic, moderately acidic and neutral pH) at [HOCl] >100 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Post‐immersion effects of rinsing times, EOW concentration, modes of application and type of EOW on impression materials, 107,161,164 and gypsum samples 107 have been measured either after direct contact or on samples obtained after rinsing hydrocolloid impressions with EOW 158,160 . The effect of rinsing time with POU acidic EOW on the surface roughness of hydrocolloid (irreversible, IRH; reversible, RH) impressions and surface hardness (scratch resistance) of resultant stone samples has been investigated 158 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations